Genomic association with pathogen carriage in bighorn sheep (Ovis canadensis). Issue 6 (2nd March 2021) - Martin, Alynn M.; Cassirer, E. Frances; Waits, Lisette P.; Plowright, Raina K.; Cross, Paul C.; Andrews, Kimberly R.
Abstract: Genetic composition can influence host susceptibility to, and transmission of, pathogens, with potential population‐level consequences. In bighorn sheep ( Ovis canadensis ), pneumonia epidemics caused by Mycoplasma ovipneumoniae have been associated with severe population declines and limited recovery across North America. Adult survivors either clear the infection or act as carriers that continually shed M. ovipneumoniae and expose their susceptible offspring, resulting in high rates of lamb mortality for years following the outbreak event. Here, we investigated the influence of genomic composition on persistent carriage of M. ovipneumoniae in a well‐studied bighorn sheep herd in the Wallowa Mountains of Oregon, USA. Using 10, 605 SNPs generated using RADseq technology for 25 female bighorn sheep, we assessed genomic diversity metrics and employed family‐based genome‐wide association methodologies to understand variant association and genetic architecture underlying chronic carriage. We observed no differences among genome‐wide diversity metrics (heterozygosity and allelic richness) between groups. However, we identified two variant loci of interest and seven associated candidate genes, which may influence carriage status. Further, we found that the SNP panel explained 55% of the phenotypic variance (SNP‐based heritability) for M. ovipneumoniae carriage, though there was considerable uncertainty in these estimates. While small sample sizes limit conclusions drawn here, our study represents one of the first to assess the genomic factors influencing chronic carriage of a pathogen in a wild population and lays a foundation for understanding genomic influence on pathogen persistence in bighorn sheep and other wildlife populations. Future research should incorporate additional individuals as well as distinct herds to further explore the genomic basis of chronic carriage. Abstract : Bighorn sheep populations impacted by infectious pneumonia may experience long‐term recovery complications due to chronically infected individuals shedding pathogen and suppressing lamb recruitment in years following outbreak events. We investigated genetic associations with the chronic carrier phenotype in bighorn sheep to better understand underlying dynamics influencing pathogen persistence in wild sheep populations.